High-Power Ultrasound in Enology: Is the Outcome of This Technique Dependent on Grape Variety? - Paula Pérez-Porras; Encarna Gómez Plaza; Leticia Martínez-Lapuente; Belén Ayestarán; Zenaida Guadalupe; Ricardo Jurado; Ana Belén Bautista-Ortín (Foods, 2023)
The disruptive effect exerted by high-power ultrasound (US) on grape cell walls is established as the reason behind the chromatic, aromatic and mouthfeel improvement that this treatment causes in red wines. Given the biochemical differences that exist between the cell walls of different grape varieties, this paper investigates whether the effect of the application of US in a winery may vary according to the grape variety treated. Wines were elaborated with Monastrell, Syrah and Cabernet Sauvignon grapes, applying a sonication treatment to the crushed grapes using industrial-scale equipment. The results showed a clear varietal effect. The wines made with sonicated Syrah and Cabernet Sauvignon grapes showed an important increase in the values of color intensity and concentration of phenolic compounds, and these increases were higher than those observed when sonication was applied to Monastrell crushed grapes, whereas Monastrell wines presented the highest concentration in different families of polysaccharides. These findings correlate with the differences in the composition and structure of their cell walls since those of Monastrell grapes presented biochemical characteristics associated with a greater rigidity and firmness of the structures.